Contrasting modernisation strategies in Germany and the USA: A comparison of concepts of production modernisation - Jürgen Wengel; Gunter Lay (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2001)
In the modernisation of production processes, German and American firms stress different aspects: a greater number of German enterprises strategically favour technology and innovation and the adaptation of products to customers' specifications. The US firms prioritise more frequently the quality of the products and a lower product price. These differences find their expression in partly diverging production engineering and production organisation. Thus the German firms underlay their orientation towards flexibility and innovation with a broader technology application in design and in the fields in which the foundations for a good supply capability are laid. In contrast to the common assumption, US industry is only partially the leader in the implementation of e-business. In the utilisation of various organisational and management concepts, German industry focuses strongly on the optimisation of product development processes and on a product-oriented segmentation of manufacturing. There is relatively less adoption by US firms of innovative forms of organisation of production.
Keywords: 330